Determinants of Economic Growth-The Case of Zimbabwe - Ncube, Trinity M (Graduate School of Business (GSB), 2019)
The paper investigated the determinants of economic growth in Zimbabwe over the period 1980 to 2017 drawing from previously identified factors as discussed in international literature which had been acknowledged as important determinants. The variables included human capital, gross fixed capital formation, unemployment, inflation and government expenditure. The study employed Unit Root Tests. The Auto Regressive Distributed Lag model was used to examine the mixed variable while the Ordinary Least Squares model and the Johansen test were used to examine all stationary and non-stationary variables respectively. In the case of co-integration, the Error Correction Model and the Causality test were run. Ultimately, the results indicated that in the long-run gross fixed capital formation has a positive influence on economic growth while human capital development has a negative influence. ECM found that in the short run there is a positive relationship between lags of economic growth, government expenditure, inflation and human capital with economic growth.